Study of the presence of fluoride anion in waters of the chili river and in waters of direct human consumption in Arequipa-Peru 2015 - Diego Lopez-Mendez (2017)
This study evaluated the fluoride concentration in water for human consumption as well as in the Chili river located in Arequipa - Peru, the methods used in the monitoring were ionic chromatography and potentiometry by ion selective electrode (ISE) of fluoride. 13 representative areas were identified for the sampling and fluoride measurement, comparing the results obtained in both methods and with the values established by the Ministry of the Environment (MINAM). The results obtained in both methods do not have a significant difference (p <0.05). The highest concentration of fluoride was obtained in water for human consumption in the Pachacutec area, obtaining an average value of 0.9835 +/- 0.0037 mg/L and 0.9780 +/- 0.0023 mg/L, respectively, for potentiometry and ion chromatography, not exceeding 1 mg/L, value established by the MINAM. Likewise, for the monitoring of the river, values of 0.2221 +/- 0.0878 mg/L, 0.4860 mg/L +/- 0.3990, 0.47796 mg/L +/- 0.2943 And 0.2970 mg/L +/- 0.0774, 0.4441 +/- 0.4090 mg/L, 0.4496 +/- 0.2914 mg/L were obtained for potentiometry and ion chromatography respectively for Captación de Sedapar, Tingo Bridge and Uchumayo Bridge.